The Influence of Corporate Governance Internal Mechanisms and Directors' Remuneration on Performance of the Company (The Case of Banking Industries in Indonesia) - Narita Pravitasari; Erna Setiany (Jurnal Keuangan dan Perbankan, 2022)
This research was conducted with the point of knowing the impact of the corporate governance internal mechanism and the remuneration of directors on performance of the company. This research focuses on the internal mechanism consisting of the board of directors’ size, internal directors, external directors, Audit Committee, Nomination and Remuneration Committee, board meeting frequency, and ownership structure. Corporate performance consists of Return on Assets (ROA) utilized to measure financial performance while Price to Book Value (PBV) is utilized to measure market performance. This research data is derived from secondary data and is sourced from the official annual report of the company. The population used in this survey was from a banking company listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020. This research used purposive sampling technique and obtained a sample of 38 companies. The analysis in this study uses a panel data regression model with the help of the EViews program. The results showed that the Audit Committee had a positive and significant influence on ROA but had no influence on PBV. The board meeting frequency has no influence on ROA, but this variable has a negative and significant influence on PBV. Meanwhile, the size of the board of directors, internal directors, external directors, Nomination and Remuneration Committee, ownership structure, and remuneration of directors have no influence on ROA and PBV.